Comparing similarities and differences between NAFLD, MAFLD, and MASLD in the general U.S. population - Zou, Haoxuan; Ma, Xiaopu; Pan, Wen; Xie, Yan (Frontiers in Nutrition, 2024)
Background: Recently, the multisociety Delphi consensus renamed nonalcoholic fatty liver disease (NAFLD) terminology (previously renamed metabolic-associated fatty liver disease (MAFLD)) as metabolic dysfunction-associated steatotic liver disease (MASLD). The aim of this study was to compare the similarities and differences between NAFLD, MAFLD, and MASLD and to clarify the impact of this new name change.Methods: A cross-sectional study of 3035 general subjects with valid vibration-controlled transient elastography data was conducted based on data from the National Health and Nutrition Examination Survey (NHANES) 2017-2020. NAFLD, MAFLD, and MASLD were defined according to the corresponding consensus criteria.Results: Using controlled attenuation parameter (CAP) ≥274 dB/m and liver stiffness measurements (LSM) ≥9.7 kPa as the cutoff values for the presence of hepatic steatosis and advanced liver fibrosis (ALF), the prevalence of NAFLD, MAFLD, and MASLD were 38.01% (95% CI 35.78-40.29%), 41.09% (39.09-43.12%), and 37.9% (35.70-40.14%), respectively, and the corresponding prevalence of ALF was 10.21% (7.09-14.48%), 10.13% (7.06-14.35%), and 10.24% (7.11-14.53%), respectively. The kappa values for the three definitions were above 0.9. The prevalence and severity of the three definitions remained similar when the sensitivity analyses were performed using different CAP thresholds. The prevalence of NAFLD, MAFLD, MASLD, and ALF increased as the number of cardiometabolic risk factors (CMRF) increased.Conclusions: Our findings highlight the consistency among the three definitions, especially between NAFLD and MASLD, so that the new consensus will not disturb the original NAFLD-related findings. Additionally, more attention should be paid to patients with a high number of CMRFs.